Breast neuroendocrine neoplasms — characteristics in contrast-enhanced mammography - Agnieszka Niewiadomska; Anna Grażyńska; Violetta Rosiek; Mateusz Winder; Joanna Szczudło-Chraścina; Michał Hrapkowicz; Anna Barczyk-Gutkowska; Aleksandra Kuźbińska; Katarzyna Steinhof-Radwańska (Endokrynologia Polska)
INTRODUCTION: Neuroendocrine neoplasms of the breast (Br-NENs) constitute a heterogeneous group of rare tumors, whose number may be underestimated. Our study aims to evaluate and compare the analysis of the radiological features of Br-NEN and carcinomas with neuroendocrine differentiation (NEDBC), which were visualized in contrast-enhanced mammography (CEM) images. MATERIAL AND METHODS: The histories of patients who, between 2015 and 2023, underwent CEM and core needle biopsy/postoperative histopathological examination confirming the nature of the lesion were retrospectively analyzed. All CEM images were acquired on two digital mammograms designed for dual-energy CEM acquisition (SenoBright et al., 3000 N. Grandview Blvd., Waukesha, WI, USA and Giotto Class, IMS Giotto, Sagittario, 5, 40037 Sasso Marconi BO, Italy). Two radiologists with at least eight years of experience describing CEM analyzed the studies and classified them into appropriate morphological categories. RESULTS: Ten patients with histopathologically diagnosed Br-NEN and 14 with NEDBC were retrospectively assessed. The mean age of patients at the time of diagnosis of Br-NEN was 56.5 years, and for NEDBC it was 67.4 years. All Br-NEN lesions and 93% of NEDBC lesions were observed as masses on low-energy CEM images. In the Br-NEN group, lesions most often had an oval shape (40%), while NEDBC lesions were irregular (43%) and obscure (43%). Multifocality and multicentricity of the tumor process were observed much more often in the Br-NEN group than in the NEDBC group. In the recombinant images, all lesions from the two groups were enhanced after intravenous administration of the iodinated contrast agent. CONCLUSION: Br-NEN and NEDBC show similar radiological features on CEM images, differing only in a few aspects.